The church historians of England: Reformation period - Pratt, Josiah (George Seeley, 1853)
v.I, pt.I. The life and defence of John Foxe. Foxe's prefaces to the Acts and monuments, and Kalender of martyrs.--v.I, pt.II-v. VIII. The acts and monuments of John Foxe, carefully revised, with notes and appendices.